Adsorption of MX2 (M = Mn, Ni, Cu, Zn, and Cd; X = Cl, Br, and I) and FeCl3 by modified silica surface with imidazolylpropyl group - Gushikem, Yoshitaka; Moreira, JoséC [UNESP] (Elsevier, 1985)
Silica gel surface modified with imidazolylpropyl group was used to adsorb MX2 (M = Mn, Ni, Cu, Zn, and Cd; X = Cl, Br, and I) and FeCl3 from ethanol and acetone solution. The adsorption capacity and the intensity of the adsorption were determined by using the Langmuir equation. The influences of the solvent, temperature, and degree of functionalization on the adsorption were also studied. The infrared spectra of the functionalized silica were recorded between 1700-1300 cm-1. The bands of the imidazole skeletal vibrations are shifted to higher frequencies upon metal-to-base nitrogen interaction. © 1985.
Keywords: SURFACES - Adsorption; ADSORPTION PROPERTIES; FUNCTIONALIZED SILICA; ORGANIC MOLECULES; SILICA GEL; SILICA